9(x-9)=-3(x-5

Simple and best practice solution for 9(x-9)=-3(x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-9)=-3(x-5 equation:



9(x-9)=-3(x-5
We move all terms to the left:
9(x-9)-(-3(x-5)=0
We multiply parentheses
9x-(-3(x-5)-81=0

See similar equations:

| 90=(x-20)x | | 87+5x=10x+17 | | m/9-1=12 | | 10b+9+3b=2 | | 2d-8d=+7-5 | | -244=-6(10p-11)-10 | | (.55+3.23)/4.2=c | | 11(11+k)+11=198 | | 12+4x-18=13 | | F(x)=9x2 | | 6.4/x=5.76 | | 2x^2-14x-312=0 | | m-m/5=141 | | -10(1-2x)-5=145 | | 4x-4x-12=-16 | | -114=-6-3(8x-4) | | 16c-3c-2=20+14c | | x/7-8=12 | | 17x^2+6x+2=180 | | -4x-6=2(x+6) | | 195=5+10(a+9) | | 9x^2+8x^2+6x=180 | | 107+23+5x=180 | | 46-g=23+7 | | X+y=16.Y=3× | | 9(1-14x)=765 | | 7x^2-20=31x | | b=3b | | 6/8x+4=21 | | 4x+3x^2=115 | | 415=6.3x | | -7/8*x=6 |

Equations solver categories